Electronic structure of Cr doped Fe3O4 thin films by X-ray absorption near-edge structure spectroscopy. (April 2018) - Chen, Chi-Liang; Dong, Chung-Li; Asokan, Kandasami; Chern, G.; Chang, C.L.
Abstract: Present study reports the electronic structures of Cr doped Fe3 O4 (Fe3-x Crx O4 (0 ≤ x ≤ 3) grown on MgO (100) substrates in the form of thin films fabricated by a plasma–oxygen assisted Molecular Beam Epitaxy (MBE). X-ray absorption near-edge structure (XANES) spectra at Cr & Fe L-, and O K-edges were used to understand the electronic structure: changes in the bonding nature, valence states, and site occupancies. Cr doping in Fe3 O4 results in the change of charge transfer, crystal structure, and selective occupation of ions in octahedral and tetrahedral sites. Such change modifies the electrical and magnetic properties due to the covalency of Cr ions. The physical and chemical properties of ferrites are strongly dependent on the lattice site, ion size of dopant, and magnetic nature present at different structural symmetry of the spinel structure. Highlights: It is of current interest particularly the explanation of the change in the magnetic properties in terms of Cr valance states as it replaces Fe. The x-ray absorption spectral changes are dependent on the electron/orbital interaction of Cr/Fe 3 d and oxygen 2 p orbitals. The results in the change of charge transfer, crystal structure, and selective occupation of ions in octahedral and tetrahedral sites.